2008
DOI: 10.1093/intimm/dxm153
|View full text |Cite
|
Sign up to set email alerts
|

Predominant donor CD103+CD8+ T cell infiltration into the gut epithelium during acute GvHD: a role of gut lymph nodes

Abstract: The existence of donor effector cell subsets responsible for either gut or skin graft-versus-host disease (GvHD) is still undetermined. We examined the trafficking and role of donor CD8(+) intra-epithelial lymphocytes (IELs) in the gut and skin epithelia concerning alpha E beta 7 integrin (CD103) expression, using a rat acute lethal GvHD model. Most CD103(+) donor cells were CD8(+) and showed a proliferative activity in the target epithelia. On the other hand, activated donor T cells in the host lymphoid tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…This view is further supported by the observation that T cells from aE null/null mice do not elicit gut graft-versus-host disease (GVHD) on transfer to wildtype allogenic recipients [24]. Zhou et al [118] confirmed these findings in a rat GVHD model, and further observed that the skin epidermis in rats during GVHD is infiltrated by an equal number of CD4 + T cells and CD8 + T cells expressing aEb7. Collazo et al [19] reported that expression of SH2 domain-containing inositol 5-phosphatase (SHIP) is required for robust expansion of donor aEb7 + CD4 + T cells during graft-versus-host and host-versusgraft responses by CD4 + T cell and limits their immunoregulatory capacity.…”
Section: Aeb7mentioning
confidence: 88%
“…This view is further supported by the observation that T cells from aE null/null mice do not elicit gut graft-versus-host disease (GVHD) on transfer to wildtype allogenic recipients [24]. Zhou et al [118] confirmed these findings in a rat GVHD model, and further observed that the skin epidermis in rats during GVHD is infiltrated by an equal number of CD4 + T cells and CD8 + T cells expressing aEb7. Collazo et al [19] reported that expression of SH2 domain-containing inositol 5-phosphatase (SHIP) is required for robust expansion of donor aEb7 + CD4 + T cells during graft-versus-host and host-versusgraft responses by CD4 + T cell and limits their immunoregulatory capacity.…”
Section: Aeb7mentioning
confidence: 88%
“…For example, recipient Peyer patches (PPs) and mesenteric lymph nodes (MLNs) may be important for the induction of gastrointestinal GVHD. 4,5 Other studies, however, have suggested a more significant redundancy among the various recipient lymphoid tissues, without a direct link between a given lymphatic organ and a specific GVHD manifestation. Notably, irradiated B6 lymphotoxin-␣ receptordeficient mice, which lack PPs and MLNs but possess an intact spleen, appear to develop intestinal acute GVHD that is similar to that of wild-type (WT) B6 recipients when given transplants across a complete major histocompatibility complex (MHC) mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…CD8 + /a E b 7 + T lymphocytes have been reported to play a critical role in mediating tubular injury following allogeneic renal transplantation (5) and in promoting renal allograft rejection (6,7). They are also involved in selective destruction of pancreatic islet allografts (8) and host intestinal epithelium during graftversus-host disease (9)(10)(11)(12), which can be prevented by CD103 deficiency (13). The a E b 7 integrin is expressed at high levels by mucosal CD8 + T lymphocytes, in particular intestinal epithelium lymphocytes (14), psoriatic skin epidermal CD8 + T cells (15), and cervicovaginal Ag-specific CTL (16).…”
mentioning
confidence: 99%